A method for performing efficient parametric dynamic analyses in large finite element models undergoing structural modifications. (15th January 2017) - Herrada, F.J.; García-Martínez, J.; Fraile, A.; Hermanns, L.K.H.; Montáns, F.J.
Highlights: A new method for accelerating dynamic analysis of large FE models in introduced. Uses information readily available from FE software stored in small files. Allows for addition of substructures, modification of properties and nonproportional damping. Typical savings in time and disk space is 1000:1, and is performed outside FE programs. The method is applied to the structure of a UAV and to a large shopping center structure. Abstract: A typical task in an engineering office is to perform parametric analyses in which the response of the structure is studied when some changes are performed. These changes may be needed in the design phase, during manufacturing or even in service. Nowadays many structural analyses employ large and detailed finite element models on which the different scenarios are considered. Parametric analyses in these structures under dynamic loading mean many code executions, require significant computer resources, result in unmanageable files and block expensive licenses of professional programs. There is a need for efficient, simple procedures which allow to perform such analyses in short time, using few resources and, if possible, releasing professional program licenses. We present a new, simple method for accelerating the parametric analyses in large structures under dynamic loading. The procedure has some similarities to model reduction methods, but no condensation is employed; in fact it can be combined with such methods for even larger efficiency gains. The proposal uses the information of the whole system of equations but only processes those nodal degrees of freedom of interest to the analyst. All needed data are easily accessed in any commercial finite element program and the process takes place entirely outside it. Modifications are introduced in a real reduced modal space and the system is re-ortogonalized. The procedure is accurate and allows for nonproportional damping, addition or elimination of stiffness, of mass and of substructures. We show the performance of the method in two study cases. One consists of modifications in the wing model of an unmanned aerial vehicle. The other one consists in the study of solutions to improve the dynamic behavior of a large civil structure.